2018
DOI: 10.1016/j.cemconcomp.2018.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing the mechanical features of clay surfaces by the absorption of nano-SiO2 particles in aqueous media. Case of study on Bronze Age clay objects

Abstract: Enhancing the mechanical features of clay surfaces by the absorption of nano-SiO2 particles in aqueous media. Case of study on Bronze Age clay objects. Cement and Concrete Composites. 93:107-117.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…have been exploited in soil stabilization; they have promising potential at enhancing the engineering properties of weak soils (e.g., clayey soil), especially, when blended with cementitious binders. For instance, nano-silica can improve the performance of clayey and silty soils by achieving small intergranular spaces resulting in further interaction with the matrix [11]. Kalhor et al [12] have stabilized clayey soil using nano-silica particles; successful enhancements have been reported for the unconfined compressive strength and the resistance to freezing-thawing cycles.…”
Section: Introductionmentioning
confidence: 99%
“…have been exploited in soil stabilization; they have promising potential at enhancing the engineering properties of weak soils (e.g., clayey soil), especially, when blended with cementitious binders. For instance, nano-silica can improve the performance of clayey and silty soils by achieving small intergranular spaces resulting in further interaction with the matrix [11]. Kalhor et al [12] have stabilized clayey soil using nano-silica particles; successful enhancements have been reported for the unconfined compressive strength and the resistance to freezing-thawing cycles.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, it has been shown that nano-materials have promising effects at improving the engineering properties of powdered materials (i.e., clay, cement). For instance, nanoparticles (nano-silica) can enhance the performance of lowdensity materials, achieving small intergranular spaces to further interact with the matrix [3]. Also, nano-silica has been proven to significantly enhance the fresh, mechanical and durability properties of cement-based materials, comprising GU or blended cements [e.g.…”
Section: Introductionmentioning
confidence: 99%